Tools design of bread production process to minimize musculoskeletal disorders based on OCRA method - Bidiawati, Ayu; Setiawati, Lestari; Kurnia, Yulia (International Journal of Engineering and Technology, 2018)
Less supportive working methods may lead operators inconvenience while working. This discomfort can be caused by a non-ergonomic work environment. Bread baking process is done manually using human energy. This work is done repeatedly for a long time, thereby posing a risk of musculoskeletal disorders. This is at risk of causing pain in some parts of the worker's body. Ergonomic work facilities and equipment are essential to minimize risk at work. The result of NBM (Nordic Body Map) questionnaire indicate that the biggest complaint is on the right back of the worker's arm and shoulders. In baking process, the operator must bend almost 90 degrees. This posture can cause health problems, especially musculoskeletal.Â Based on observations using the OCRA (Occuptional Repetitive Action) method, the OCRA index value for the right hand is 8.56 and for the left hand is 7.84, with the red area and the average category of risk. Therefore, a trolley is designed in this study as a tool to minimize musculoskeletal complaints, using workers anthropometric data.Â Â